2022
DOI: 10.3390/su14148490
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Multi-Satellite Precipitation Products over the Himalayan Mountains of Pakistan, South Asia

Abstract: Performance assessment of satellite-based precipitation products (SPPs) is critical for their application and development. This study assessed the accuracies of four satellite-based precipitation products (PERSIANN-CDR, PERSIANN-CCS, PERSIANN-DIR, and PERSIANN) using data of in situ weather stations installed over the Himalayan Mountains of Pakistan. All SPPs were evaluated on annual, seasonal, monthly, and daily bases from 2010 to 2017, over the whole spatial domain and at point-to-pixel scale. The assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 55 publications
(102 reference statements)
1
10
0
Order By: Relevance
“…The results of previous studies also indicated that the performance of SPPs was strongly influenced by the topography and climatic conditions of the study area [32][33][34]. For instance, Nadeem et al [22] assessed the variety of SPPs over diverse topographic and climatic conditions. The findings of their study also documented that the accuracy of satellite precipitation products showed significant variation with respect to in-situ topography and climatic conditions.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…The results of previous studies also indicated that the performance of SPPs was strongly influenced by the topography and climatic conditions of the study area [32][33][34]. For instance, Nadeem et al [22] assessed the variety of SPPs over diverse topographic and climatic conditions. The findings of their study also documented that the accuracy of satellite precipitation products showed significant variation with respect to in-situ topography and climatic conditions.…”
Section: Discussionmentioning
confidence: 97%
“…The evaluation of soil moisture products (SM2Rain, SM2Rain-ASCAT, SM2Rain-CCI, and GPM-SM2Rain) was assessed using in-situ ground observations. In the validation process, the methodology of previously published studies [3,22] was used. We only considered SPP grids with at least one benchmark measuring station.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations